Mortality Among Pediatric Patients With Acute Lymphoblastic Leukemia in Sweden From 1988 to 2017 - Björk-Eriksson Thomas; Boström Martina; Bryngelsson Ing-Liss; Lähteenmäki Päivi M; Jarfelt Marianne; Kalm Marie; Olsson Daniel S (AMER MEDICAL ASSOC, 2025)
Importance: Acute lymphoblastic leukemia (ALL) constitutes 20% to 30% of all pediatric cancers. The 5-year overall survival among pediatric patients with ALL in high-income countries such as Sweden is currently more than 90%, but long-term unselected nationwide mortality data and mortality data in relation to the general population are lacking.
Objective: To compare mortality between pediatric patients with ALL and the general population during a 30-year period in Sweden and to assess the incidence of ALL in Sweden.
Design, setting, and participants: This cohort study included pediatric patients (aged <18 years) with a morphologically verified ALL diagnosis in the Swedish Cancer Register and/or at least 2 ALL diagnoses in the Swedish National Patient Register between January 1, 1988, and December 31, 2017. Data were cross-linked to the Swedish Cause of Death Register. Data were analyzed from May 2019 to January 2022.
Main outcomes and measures: The main outcomes were mortality among patients with ALL compared with that in the general population and mortality in different subgroups within the cohort. Standardized mortality ratios (SMRs) were calculated using the general Swedish population as a reference. Within-cohort survival analyses were performed.
Results: A total of 2397 patients (1354 [56%] male; mean [SD] age at diagnosis, 6.1 [4.7] years) were included in the study. The mean (SD) incidence of pediatric ALL during the study period was 4.11 (0.60) cases per 100 000 persons per year (females, 3.68 [0.65] cases per 100 000 persons per year; males, 4.52 [0.81] cases per 100 000 persons per year; P < .001). The observed number of deaths among pediatric patients with ALL was 409 vs the 9.5 deaths expected in the general population, resulting in an overall SMR of 43.1 (95% CI, 39.0-47.5); females had a higher SMR than males (57.8 [95% CI, 49.5-67.2] vs 34.5 [95% CI, 32.0-41.4]; P < .001). Analysis within the cohort showed a continued decrease in survival throughout the 30-year follow-up. The association between calendar year of ALL diagnosis, corresponding with different ALL treatment protocols, and mortality showed the lowest survival for the 1988-1991 group and the highest for the 2008-2017 group (χ2 = 20.3; P < .001).
Conclusions and relevance: In this cohort study, a consistently high SMR was seen among pediatric patients with ALL. Within the ALL cohort, survival evolved to a similar extent as in the young general population of Sweden. Furthermore, survival among patients with ALL decreased throughout the whole follow-up period without any trend difference after the 5-year follow-up time point. The changes in ALL treatment protocols were associated with overall improved absolute survival over time.